DIGITAL SEARCH AS A NEW INVESTIGATIVE ACTION ACCORDING TO THE NEW CRIMINAL PROCEDURE CODE OF THE REPUBLIC OF ARMENIA - Petrosyan, Lara (State and Law, 2023)
The new Criminal Procedure Code of the Republic of Armenia envisages digital search as a new investigative action in order to make the search of electronic data stored in computer systems effective. In the submitted article, the author discusses the necessity of defining digital search as an independent investigative action in the light of peculiarities of electronic data, as well as analyzes the benefits of envisaged legal regulations. At the same time, the author identifies a number of shortcomings based on international standards for search and seizure of computer data.